Enzymes involved in DNA ligation and end-healing in the radioresistant bacterium Deinococcus radiodurans - Blasius, Melanie (BioMed Central, 2007)
BACKGROUND: Enzymes involved in DNA metabolic events of the highly radioresistant bacterium Deinococcus radiodurans are currently examined to understand the mechanisms that protect and repair the Deinococcus radiodurans genome after extremely high doses of γ-irradiation. Although several Deinococcus radiodurans DNA repair enzymes have been characterised, no biochemical data is available for DNA ligation and DNA endhealing enzymes of Deinococcus radiodurans so far. DNA ligases are necessary to seal broken DNA backbones during replication, repair and recombination. In addition, ionizing radiation frequently leaves DNA strand-breaks that are not feasible for ligation and thus require end-healing by a 5'-polynucleotide kinase or a 3'-phosphatase. We expect that DNA ligases and end-processing enzymes play an important role in Deinococcus radiodurans DNA strand-break repair. RESULTS: In this report, we describe the cloning and expression of a Deinococcus radiodurans DNA ligase in Escherichia coli. This enzyme efficiently catalyses DNA ligation in the presence of Mn(II) and NAD(+ )as cofactors and lysine 128 was found to be essential for its activity. We have also analysed a predicted second DNA ligase from Deinococcus radiodurans that is part of a putative DNA repair operon and shows sequence similarity to known ATP-dependent DNA ligases. We show that this enzyme possesses an adenylyltransferase activity using ATP, but is not functional as a DNA ligase by itself. Furthermore, we identified a 5'-polynucleotide kinase similar to human polynucleotide kinase that probably prepares DNA termini for subsequent ligation. CONCLUSION: Deinococcus radiodurans contains a standard bacterial DNA ligase that uses NAD(+ )as a cofactor. Its enzymatic properties are similar to E. coli DNA ligase except for its preference for Mn(II) as a metal cofactor. The function of a putative second DNA ligase remains unclear, but its adenylyltransferase activity classifies it as a member of the nucleotidyltransferase family. Characterization of another protein from the same operon revealed a 5'-polynucleotide kinase with a possible role in DNA strand-break repair.